Knowledge, attitudes and beliefs towards compulsory vaccination: a systematic review. Issue 4 (3rd April 2019) - Gualano, MR; Olivero, E; Voglino, G; Corezzi, M; Rossello, P; Vicentini, C; Bert, F; Siliquini, R
ABSTRACT: Currently, many countries are dealing with groups refusing available recommended vaccinations. Despite several studies having demonstrated the efficacy of mandatory vaccinations in ensuring herd immunity, opposition is widespread. The aim of our study was to systematically review published studies evaluating attitudes towards mandatory vaccination programs. PubMed and Scopus scientific databases were searched and 4, 198 results were returned, of these 29 met the inclusion criteria. Twenty-two studies assessed attitudes towards mandatory vaccination programs in general, while 9 papers focused specifically on the Human Papilloma Virus (HPV) vaccine. Most of the studies were performed in Europe and North America. According to the assessed studies, the majority of the population seems to be in favour of compulsory vaccinations, although attitudes differed among studies. The results presented in this review could be an important starting point to further understand the issue of vaccine hesitancy and support the implementation of effective vaccination strategies.